Environmental Sampling and Analysis - Mimi Suliza Muhamad (Penerbit UTHM, 2023)
This text book introduces the fundamental knowledge on environmental sampling and analysis that is essential for students of Bachelor of Civil Engineering Technology (Environment), UTHM. Chapter 1 present the topic on sampling plan which include sampling protocol, planning a sampling event, and selection of appropriate methodology. Chapter 2 present the topic on sampling method which covers the topics of quality control of sample, sampling location, and types of environmental sampling including water, air, and soil sampling. Chapter 3 is the topic on sample preservation and storage. This chapter discusses on preservation techniques, sample storage, disposal, and sample holding time. Chapter 4 is the topic about microbiological analysis which include multiple tube method, pour plate method, membrane filtration method, and pathogen analysis. Chapter 5 present the topic on analytical data in which discusses how the collected environmental data is analyse. This chapter include the statistical for environmental data, errors in analytical data, as well as standardization and calibration. Chapter 6 is the topic on instrumentation which explain the instrument and method used to analyse sample. This chapter discuss on method and analytical instrument such as spectrophotometry, electron microscopy and elemental analysis, Fourier transform infrared, total organic carbon analyzer, atomic absorption spectrophotometer, ion chromatography, solid/liquid chromatography, gas/liquid chromatography and mass spectrometry.